Bevacizumab/PD-1 inhibitor plus chemotherapy as first-line treatment of advanced non-squamous non-small-cell lung cancer - Jing Wang; Qin Chen; Xinyue Wang; Dingzhi Huang; Richeng Jiang (Becaris Publishing Limited, 2023)
Aim: To compare the effectiveness of PD-1 inhibitor or bevacizumab plus chemotherapy in advanced nonsquamous non-small cell lung cancer (nsNSCLC). Methods: We retrospectively collected data for patients with advanced nsNSCLC who underwent first-line treatment with PD-1 inhibitor or bevacizumab plus chemotherapy (IC and BC groups). Propensity score matching (PSM) was adopted to balance covariates. Results: 278 patients were enrolled, after PSM (n = 104/group), the objective response rate was 45.1% and 24.0% in the IC and BC groups (p = 0.001).Median progression-free survival (PFS) was 13.5 and 8.2 months (p = 0.007), and duration of response was 14.8 versus 8.1 months (p = 0.007), respectively. In subgroup analysis, the PFS for those patients with PD-L1≥1% (16.2 vs 6.8 months, p = 0.000) was significantly longer in the IC group than that in BC group, but not in the PD-L1<1% subgroup (8.9 vs12.7 months, p = 0.719). Conclusion: PD-1 inhibitor plus chemotherapy was superior to bevacizumab plus chemotherapy as firstline treatment for advanced nsNSCLC, which is debatable for patients with PD-L1<1%.